What Do We Know About Bacterial Infections in Hidradenitis Suppurativa?—A Narrative Review - Zuzanna Świerczewska; Wioletta Barańska-Rybak (Antibiotics)
Background/Objectives: Hidradenitis suppurativa is an inflammatory skin condition of the pilosebaceous unit of a chronic, painful, and progressive nature. It affects intertriginous parts of the body, including the axillae, groin, submammary region, and anogenital region. The risk of infection in HS patients is not well understood. Thus, presenting the most recent findings in the study of bacterial infections in relation to hidradenitis suppurativa was the objective of this review. Methods: The presented article is a narrative review. The PubMed and Scopus databases were searched for articles applicable to this review. All types of study design were included in this review. Results: Among reported infections in patients with HS, Fournier’s gangrene, osteomyelitis, Clostridium difficile infection, and biofilm were significant. Attention should also be paid to post-procedural infections. Conclusions: A wide range of bacterial infections, from localized purulent infections to serious systemic consequences, can affect patients with HS. Comorbid diseases like diabetes mellitus and obesity change the cutaneous microbiota and produce a pro-inflammatory systemic milieu, which makes the disease more severe and makes HS patients more susceptible to infections. Additionally, those with untreated or unmanaged HS are more likely to experience infectious complications.